Comparative Analysis of the Effectiveness of Organic and Inorganic Nitrogen Sources on Potato Yield and Soil Fertility - Karkee, Suraj Singh; Bishwokarma, Subas (Journal of Agriculture and Environment, 2023)
Potato is a vital food source for the high hills of Nepal. The crop requires the right amount of nutrient at the appropriate time for optimal growth and production. However, the low availability, high cost, and inappropriate timing of applying nitrogenous fertilizers like urea have made it challenging for farmers to use the correct amount in their fields. Therefore, affordable and renewable sources of plant nutrients should be used to supplement chemical fertilizers. In addition to this, using organic sources can improve soil properties. To determine the effects of nitrogen supplied through different sources, an experiment was conducted in a randomized block design. There were eight treatments, each with a different combination of nitrogen supplied through urea and various organic sources as N1(100% rec N via Urea), N2 (50 % rec N via FYM + 50 % rec N via Urea), N3 (50 % rec N via PM + 50 % rec N via Urea), N4(50 % rec N via GM + 50 % rec N via Urea) , N5 (75 % rec N via FYM + 25 % rec N via Urea), N6 (75 % rec N via PM + 25 % rec N via Urea), N7 (75 % rec N via GM + 25 % rec N via Urea), N8 (Farmer practices (FYM 10 t ha-1)). The yield of potato tubers was significantly higher when recommended nitrogen was applied 50% through organic manure like poultry, FYM, and goat, and 50% through urea than other treatments, including farmer practice of using 10 t ha-1 FYM. However, the yield was statistically at par with nitrogen via sole urea. Additionally, the application of organic manures led to an increase in soil properties such as organic manure content, nitrogen, phosphorous, and potassium content. In conclusion, application of recommended nitrogen as 50% via organic manures like poultry, FYM, and goat, and 50% N via urea can enhance potato yield while also positively affecting soil properties.